PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN MENULIS TEKS PERSUASI SISWA KELAS VIII SMP SWASTA AL ITTIHADIYAH TAHUN PEMBELAJARAN 2022-2023 - Endah Tri Agusta Ritonga; Fata Ibnu Hajar (Jurnal Inovasi Penelitian, 2023)
This study aims to find out how the application of problem-based learning models to the ability to write persuasive texts at Al Ittihadiyah Private Middle School. The research subjects were class VIII students of Al Ittihadiyah Private Middle School in the 2022-2023 Academic Year, with a total of 27 students, consisting of 12 male students and 15 female students. The method used in this study is a problem-based learning model with media images. From the results of this study it was found that the learning outcomes of class VIII students applying the problem-based learning model to the ability to write persuasive texts for class VIII students of Al Ittihadiyah Private Middle School in the 2022-2023 academic year in writing persuasive texts before using the problem-based learning model were very low, it has been proven on the results of the pre-test that has been carried out by researchers who get as many as 15 students do not complete. It can be seen that the application of the problem based learning model with media images has an effect on increasing student activity in learning persuasive text skills. In cycle I the average score was 63% with Enough criteria. In cycle II the average score was 93% with Very Good criteria. On student learning outcomes after using the problem based learning model in the first cycle as many as 17 students were declared complete and in the second cycle as many as 25 students were declared complete.